Effect of Powder Shape and Sintering Temperature on the Preparation of Ni-Based Porous Metal - Yu-Jeong Yi; Min-Jeong Lee; Hyeon-Ju Kim; Sangsun Yang; Manho Park; Byoung-Kee Kim; Jung-Yeul Yun (Archives of Metallurgy and Materials, 2019)
Usually porous metals are known as relatively excellent characteristic such as large surface area, light, lower heat capacity, high toughness and permeability for exhaust gas filter, hydrogen reformer catalyst support. The Ni alloys have high corrosion resistance, heat resistance and chemical stability for high temperature applications. In this study, the Ni-based porous metals have been developed with Hastelloy powder by gas atomization and water atomization in order to find the effects of powder shape on porous metal. Each Hastelloy powder is pressed on disk shape of 2 mm thickness with 12 tons using uniaxial press machine. The specimens are sintered at various temperatures in high vacuum condition. The pore properties were evaluated using Porometer and microstructures were observed with SEM.